Financial strategy and practice to climate change adaptation in the real estate sector: case study on YTL Land & Development Bhd. (YTL L&D) - Punitha, Aresamy (2021)
The real estate industy is highly influenced by the aspects of climate change in Malaysia. As climatic events have direct adverse impacts on the monetary performance of real estate sectors in Malaysia, it also increases the business risk for these organizations. Therefore, to maintain price stability, higher equity,market risk premium and/or higher dividend is required. This risk premium and cost of equity, dividend, can be considered as the climate change adaptation cost at the stock market level. This cost helps real estate to maintain performance at the stock market level. The current study aims to explore to understand possible affects of climate change on Malaysian real estate firms. The respondents were nine YTL Land and Development personnel who worked in the operating sector and were managers and important employees in the department. The study utilized qualitative method and classifying the interview results. The results show that vulnerability, infestation, risk of harsh environment, and increasing temperature, all may have negative influence on real estate.To deal with those risks, policy makers and firm managers need to take different initiatives and spend in many ways. Moreover the respondents stressed the importance of insurances, policy makers understanding, climate change, risk assessment, and resilience to support climate change adaptation to reduce potential impacts in major findings from the study.This research adds to a deeper understanding of how climate adaptation activities, might influence real estate industry in combination with storm characteristics and risk perception, might improve coastal construction resiliency. The findings data from construction industry, as well as information of regional adaptation actions, can be used by asset owners and managers to improve asset resilience and informs around common adaptation goals. A limitation of this research may be the minor number of respondents who were interviewed, which totaled only nine people in this study. Nine responses are comprised of important members of the property, project, finance, and operations teams. This number may appear to be insignificant in some instances.